The Effect of Receiving Treatment Within a Clinical Trial Setting on Survival and Quality of Care Perception in Advanced Stage Non–Small Cell Lung Cancer. (April 2016) - Abu-Hejleh, Taher; Chrischilles, Elizabeth A.; Halfdanarson, Thorvardur R.; Simon, Christian; Pendergast, Jane F.; Jiang, Dingfeng; Smith, Carmen J.; Porter, Aaron T.; Carter, Knute D.; Wallace, Robert B.
Abstract : Objectives: Treatment outcomes of advanced stage (IIIB and IV) non–small cell lung cancer (NSCLC) are poor. In this study, we explore the survival outcomes and the perception of the quality of care delivered in stage IIIB and IV NSCLC patients treated within versus outside a clinical trial. Materials and Methods: Data were obtained from the Cancer Care Outcomes Research and Surveillance Consortium (CanCORS). Baseline characteristics according to clinical trial participation were determined. The association between clinical trial enrollment and survival was assessed using a Cox proportional hazard model after adjusting for age, income, primary data collection and research site, comorbidities, self-reported performance status, presence of brain metastasis, stage IIIB versus IV, and cancer histology. Results: Of 815 stage IIIB and IV NSCLC patients, 56 (7%) were enrolled in clinical trials. Median survival for the patients treated within versus outside a clinical trial was 20.5 versus 16.7 months, respectively ( P =0.21). Using a multivariate survival model, clinical trial enrollment did not correlate with longer survival ( P =0.81). Comparing patients according to clinical trial enrollment, patients treated within a clinical trial setting perceived a better overall quality of care ( P <0.01). Conclusions: Management of stage IIIB and IV NSCLC patients within a clinical trial setting conveyed a perception of superior care that did not translate into survival benefit. These findings suggest that providing cancer care within a clinical trial should not imply a survival benefit when counseling stage IIIB and IV NSCLC patients about entering clinical trials. Abstract : Supplemental Digital Content is available in the text.